RESEARCHING DEIXIS OF JOE BIDEN'S SPEECH ON “THE COVID-19 VACCINATION PROGRAM AND THE EFFORT TO DEFEAT COVID-19 GLOBALLY” (2021) - Vina Christina Luhulima; Dewanto Dewanto; Ari Astutik (Fakultas Bahasa & Sastra Universitas Wijaya Putra, 2022)
This study intends to describe five forms of use of deixis by Levinson (1983) in Joe Biden's speech. Aims to determine the types of deixis and interpret the reference meaning of the deixis in Joe Biden's speech. The data used in this study are all taken from the contents of Joe Biden's Speech. The researcher was interested in taking Joe Biden's speech as data because Joe Biden is a world-famous person and a leader of the United States so the contents of his speech will be of interest to the whole world. Data retrieval sources are available in two forms, the first on the official Whitehouse website and the second on YouTube. researchers took data on the Whitehouse website. The research was conducted by applying a qualitative descriptive method in the research. After doing research, as a result, it was found that the five types of deixis, namely person, place, time, discourse, and social deixis were all used in Joe Biden's speech by referring to different objects.